Regenerative endodontic therapy for external inflammatory lateral resorption following traumatic dental injuries: Evidence assessment of best practices. (27th September 2022) - Lin, Shaul; Moreinos, Daniel; Wisblech, Dekel; Rotstein, Ilan
Abstract: Background: External inflammatory lateral resorption (EILR) following dental trauma is a severe complication that can lead to significant root loss and tooth extraction. Objective: The aim of this project was to review current evidence in the literature on regenerative endodontic therapy (RET) for EILR following traumatic injuries and assess the best treatment practices. Methods: Publications appearing in PubMed, from January 1, 2001 to January 9, 2022 were studied. Inclusion criteria were: (a) Publications in English; (b) Publications on RET and EILR; (c) Teeth subjected to dental trauma; and (d) Presence of intracanal bleeding and blood clots. Exclusion criteria were: (a) Conference proceedings; (b) Lectures; (c) Abstracts; and (d) Letters to editor; (e) Non‐English publications. Results: 355 publications were analysed. Nine met all inclusion criteria. In 10 (58.8%) teeth, triple antibiotic paste was used for an average of 26 days. Double antibiotic paste was used in 3 (17.6%) teeth for an average of 14 days. In 3 (17.6%) cases, calcium hydroxide (Ca(OH)2 ) was used for 14 days and negative pressure irrigation was applied once on 1 (6%) tooth. Discussion: Using RET to treat EILR has some advantages compared to long term CA(OH)2 dressing. RET requires shorter dressing time compared to CA(OH)2 . This can significantly improve patient compliance. Additionally, in immature teeth, RET helps to arrest root resorption leading to continued root maturogenesis and revascularization. It is recommended that a meticulous follow‐up should be conducted when RET is performed to assure early detection of treatment failure. Conclusions: RET appears to be a good treatment modality producing biologic repair and improving prognosis in cases of EILR in post‐traumatic tooth/pulp injuries. The key limitation of this study is that all publications included were either case reports or case series that usually tend to report successful outcome.